2009
DOI: 10.1364/oe.17.004773
|View full text |Cite
|
Sign up to set email alerts
|

Opto-VLSI-based photonic true-time delay architecture for broadband adaptive nulling in phased array antennas

Abstract: This paper proposes a novel Opto-VLSI-based tunable true-time delay generation unit for adaptively steering the nulls of microwave phased array antennas. Arbitrary single or multiple true-time delays can simultaneously be synthesized for each antenna element by slicing an RFmodulated broadband optical source and routing specific sliced wavebands through an Opto-VLSI processor to a high-dispersion fiber. Experimental results are presented, which demonstrate the principle of the true-time delay unit through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Since the demonstration of an optically steered phased array antenna in 1991, 1 the study of tunable microwave time delay lines realized by photonics has become a hot topic within the developing research area of microwave photonics. 2 A common scheme exploits dispersion, with the time delay being varied by tuning the laser wavelength and propagating through high dispersion fibers 3,4 or chirped fiber gratings. [5][6][7] This scheme is, however, relatively bulky and complex.…”
mentioning
confidence: 99%
“…Since the demonstration of an optically steered phased array antenna in 1991, 1 the study of tunable microwave time delay lines realized by photonics has become a hot topic within the developing research area of microwave photonics. 2 A common scheme exploits dispersion, with the time delay being varied by tuning the laser wavelength and propagating through high dispersion fibers 3,4 or chirped fiber gratings. [5][6][7] This scheme is, however, relatively bulky and complex.…”
mentioning
confidence: 99%
“…4. The free-spectral range (FSR) of the RF response is inversely proportional to the true-time delay between adjacent wavebands (Juswardy et al 2009) and the experimental results shown in Fig. 7 demonstrates the simultaneous generation of 7 wavebands with 1.8-4 nm separation between adjacent waveband, corresponding to an arbitrary inter-waveband true-time delay of 0.7 to 1.5 ns.…”
Section: Simulation and Experimental Resultsmentioning
confidence: 87%
“…The diffraction (or steering) angle for an Opto-VLSI processor, α m , is given by Juswardy et al (2009):…”
Section: Principle Of Opto-vlsi Based Ttd Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, for an N-element broadband phased array, the synthesis of (N-1) broadband nulls can be achieved if the beamformer of the antenna can adaptively generate and combine (2 N-1 -1) delayed versions of the RF signals received by the antenna elements [2] as illustrated in Fig. 1.…”
Section: Principle Of Broadband Null Steeringmentioning
confidence: 99%